Balloon Dilatation of Laryngotracheal Stenosis: Hospital Ampang Experience - Loo, LY; A, Mawaddah; H, Shahrul; A, Khairullah (IIUM Medical Journal Malaysia, 2017)
The upper airway is a crucial structure. It becomes a grave problem should it be narrowed. Several methods of treatment were rendered for patients with laryngotracheal stenosis. We share our experience with the combination total intravenous anaesthesia and apneic pause technique with or without steroid injection. Four cases of laryngotracheal stenosis were observed in Hospital Ampang: two adult and two paediatric cases. Age, gender, causative factor, stenosis segment length, grade or severity were observed before and after dilatation, number of dilatation were observed and compared. The outcome measures are decannulation and avoidance of tracheostomy. All cases had improvement of symptoms. Half or 50% of the patient required repeated balloon dilatations. The paediatric cases successfully avoided tracheostomy while the adult cases successfully decannulated with no complication from the procedure. Balloon dilatation by total intravenous anaesthesia coupled with apneic method is a safe and effective method of treatment for the narrowed airway.